Me adiciona.com: Ensino de arte+tecnologias contemporâneas+escola pública - Geraldo Freire Loyola (2009)
The present study aims at investigating possibilities both of computer use and of web particularities as a means to explore, by the teachers, activities in the Art teaching. The computer with internet connection has been progressively transforming itself in unifying equipment of several media, reducing the borderlines between different supports. Theeasiness and the high-speed access to information and images also result in a distinct dynamics towards knowledge and, with the broadband, the services of actions and interactive ideas popularized and the on line milieu has developed. The computer users abandoned a passive behaviour and began to produce, manage and interact with the contents in the net, promoting thus cultural and conceptual changes in the use of web. The Art teachers should be aware of these technologies and present them to their students, since the interactivity resultsin experiments which combine potentialities for knowledge construction.